Analisa Model Hidrologi dan Hidrolika di Area Lereng Kritis Ruas Jalan Patikraja – Rawalo, Banyumas - Ratih Pujiastuti; Tenardhy Aryarama Wijaya; Agung Hari Wibowo; Hikmah Monica; Alif Agus Tiyanto (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2026)
This study analyzes the hydrological and hydraulic characteristics of the Patikraja-Rawalo road section in Banyumas Regency, which is adjacent to the Serayu River and is prone to landslides. The main focus is on watershed delineation (DAS), design rainfall determination, flood discharge calculation, floodwater elevation determination, and scour depth. Using historical rainfall data and hydrological modeling (Nakayasu and HEC-HMS) and hydraulic modeling (HEC-RAS 2D), the 50-year design flood discharge is 2,217.80 m³/s and a maximum scour depth of 2.51 m. These results provide a crucial basis for designing retaining walls to ensure road stability.